对于任意正整数n,由Bernoulli不等式有
\(\frac{x_{n+1}}{x_n}=\frac{n^n(n+2)^{n+1}}{(n+1)^{2n+1}}\)
\(=(\frac{n^2+2n}{(n+1)^2})^n\frac{n+2}{n+1}\)
\(=(1-\frac{1}{n^2+2n+1})^n\frac{n+2}{n+1}\)
\(≥(1-\frac{n}{n^2+2n+1})\frac{n+2}{n+1}\)
\(=\frac{n^3+3n^2+3n+2}{n^3+3n^2+3n+1}\)
\(≥1\)
对于任意正整数n≥2
\(\frac{y_{n-1}}{x_n}=\frac{n^{2n+1}}{(n-1)^n(n+1)^{n+1}}\)
\(=(\frac{n^2}{(n^2-1})^n\frac{n}{n+1}\)
\(=(1+\frac{1}{(n^2-1})^n\frac{n}{n+1}\)
\(≥(1+\frac{n}{(n^2-1})\frac{n}{n+1}\)
\(=\frac{n^3+n^2-n}{n^3+n^2-n-1}\)
\( ≥1\)
因此对于任意正整数你都有\(2=x_1≤x_n≤y_n≤y_1=4\),所以他们都是收敛的。
证明数列\(x_n=(1+\frac{1}{n})^n和y_n=(1+\frac\{1}{n})^{n+1}\)收敛
原文:https://www.cnblogs.com/valar-morghulis/p/13834064.html